ROUND TABLE WITH PETŐFI JÁNOS SÁNDOR – TEXT LINGUISTICS, TEXT SEMIOTICS, CORPUS LINGUISTICS - Barbera, Manuel (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2018)
In the afternoo of February 27, 2004 Petőfi János Sándor received an honorary degree in Foreign Languages and Literatures from the University of Turin. In the morning of the same day, again at the University of Turin, the local Doctorate in Linguistics, Applied Linguistics and Linguistic Engineering organized a round table with him on the topic “Text Linguistics, Text Semiotics, Corpus Linguistics: What Relationships?”. In addition to Petőfi, around which the event was built, intervened Ugo Volli, Carla Marello, Dario Corno, Maria Teresa Prat Zagrebelsky, Manuel Barbera and some doctoral students, including Adriano Allora, Stefania Ferraris and Alessandro Panunzi, as well as other colleagues and PhD students of Turin and Macerata Universities.